Drinking Behavior and Its Prevalence in Grade 10th Students - Hosiri, Tikumporn; Sittisun, Chuleekorn; Limsricharoen, Kanokwan (Journal of the Psychiatric Association of Thailand, 2016)
ABSTRACT Objectives: To study the prevalence of alcohol drinking behavior among grade 10th students in a northern province of Thailand and to explore factors associated with drinking behavior. Method :A cross-sectional descriptive study was conducted in 538 randomly sampled participants. The self-rated questionnaires included demographic data, drinking behavior, and The Alcohol Use Disorder Identification Test (AUDIT). Descriptive statistics was used for data analysis. Results: The prevalence of alcohol drinking among grade 10th students was 44.2%. The percentages of low-risk, hazardous, harmful, and high-risk alcohol drinking pattern were 67.9%, 22.8%, 3.8%, and 5.4%, respectively. Mean age of their first exposure to alcohol was 14.5 years old. Reasons for drinking were experiment, socializing and influenced by peers. The most popular type of alcohol was beer; the popular shops for sale alcohol were grocery and convenience stores; the popular drinking places were their peer’s house and their own house; and most of them had history of drinking in family. The factors associated with drinking behavior included male, GPA ≤ 3.00, divorced/ separated/widowed parents, lack of accountable tasks in their free time and history of drinking in family. Conclusion: Nearly a half to the grade 10th students have alcohol drinking. It was easy for them to buy alcohol and find a place to drink. Factors associated with drinking behavior were male gender, academic problem (GPA<3), parental broken relationship, lack of accountable tasks during free time and history of drinking in family.